Electroacupuncture Pretreatment as a Novel Avenue to Protect Brain against Ischemia and Reperfusion Injury. (26th April 2012) - Li, Xin; Luo, Peng; Wang, Qiang; Xiong, Lize
Abstract : Electroacupuncture (EA) pretreatment is a recent observation which has been shown to induce ischemic tolerance mimicking the ischemic pretreatment, suggesting that EA pretreatment may be a promising preventive strategy for the patients with high risk of acute ischemia/reperfusion injury. It was first described in the brain, then in the heart where EA stimulation at acupoint prior to ischemia led to neuroprotection and myocardial protection and induced rapid and delayed ischemic tolerance. Then the optimal parameters and acupoint specificity of EA pretreatment to induce protective effect were proved. Many studies have shown that protective mechanisms of EA pretreatment may involve a series of regulatory molecular pathways including activity enhancement of antioxidant, regulation of the endocannabinoid system, involvement of beta -adrenergic receptor, and postreceptor signaling pathway, inhibition of apoptosis. Recently, the neuroprotective and cardioprotective effect of EA pretreatment had been demonstrated in patients undergoing craniocerebral tumor resection or heart valve replacement surgery. Thus, the purpose of this paper is to collect the evidence for the neuroprotective effect of EA pretreatment, to summarize the proposed protective mechanisms of EA pretreatment, and to discuss the possibility of EA pretreatment as a new preventive strategy for patients with high risk of ischemia in clinic.